Gastroparesis: Prevalence, Clinical Significance and Treatment - Michael Horowitz; Yu-Chung Su; Christopher K Rayner; Karen L Jones (Canadian Journal of Gastroenterology)
The application of novel techniques to quantify gastric motor function and gastric emptying has yielded important insights into the prevalence, pathogenesis and clinical sequelae of gastroparesis. Both acute and chronic gastroparesis occur frequently; gastric emptying of solids is delayed in 30% to 50% of patients with diabetes mellitus, functional dyspepsia and gastroesophageal reflux disease. While many patients with gastroparesis experience upper gastrointestinal symptoms that adversely affect quality of life, the concept that symptoms are inevitably the direct outcome of delay in gastric emptying is now recognized to be overly simplistic. In contrast, the potential impact of gastroparesis on oral drug absorption and blood glucose control in patients with diabetes mellitus has probably been underestimated. While the use of prokinetic drugs (cisapride, domperidone, metoclopramide and erythromycin) forms the mainstay of therapy in symptomatic patients with gastroparesis, a number of novel pharmacological therapies are being evaluated, and preliminary studies using gastric pacing show promise.